Grandmothers Against Removals. - Grandmothers Against Removals (Gunnedah, New South Wales : Grandmothers Against Removals, 2014)
"Gunnedah grandmothers fight against the removal of Indigenous kids. The group Grandmothers Against Removals (GMAR) was formed in January in an effort to highlight the process of removal used by the New South Wales Department of Children's Services."
Title from title screen (viewed on 9 April 2015)
Mode of access: Available online. Address as at 10/04/2015
Selected for archiving
Keywords: Stolen generations (Australia); Australian